A rare case of takotsubo syndrome within the first day after heart transplantation - Al Humaid, Mohammed; Ahmed, Mawada; Galzerano, Domenico; Al Hussein, Mosaad; Al Admawi, Mohammed; Al Buraiki, Jehad; Alsergani, Hani; Vriz, Olga (Monaldi Archives for Chest Disease, 2019)
A 39-year-old woman underwent heart transplantation (HTx) for advanced heart failure. The donor was a 36-year-old young woman without past medical history. The first day after HTx, T-waves changes were noted. Echocardiography revealed akinesia/dyskinesia of all basal segments of the two ventricles. Coronary catheterization plus biopsy were done 7 days later showing no coronary obstruction, no rejection and complete recovery of wall motion abnormalities on echocardiogram, suggesting biventricular inverted takotsubo syndrome (TTS). This is a case of TTS during the first day after HTx, with completely denervated heart but because of the inotropic drug support it still represents a target for catecholamine-induced cardiac dysfunction.